Télécollaborations (inter)culturelles sur Facebook - Elsa Chachkine (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This article deals with a project of cultural exchange on a Facebook page between students of the Cnam (France) and students of the University of Ulyanovsk (Russia). The project of (inter)cultural telecollaboration is grounded in Vygotski's (1934/1997) socio-cultural theory. First, an analysis of the types of knowledge exchanged between participants as well as the skills mobilised for intercultural communication during the discussions is carried out. To achieve this, the typology of socio-cultural competences for intercultural communication developed by Anquetil (2006) is adopted. Then, the innovative character of the project is examined, relating it to the main academic pedagogical innovations of the moment identified by Fabre (2015), and its effectiveness (Tricot, 2017), another purpose of pedagogical innovation, is considered.